Addressing Household Indebtedness: Monetary, Fiscal or Macroprudential Policy? - Sami Alpanda; Sarah Zubairy (Bank of Canada, 2014)
In this paper, we build a dynamic stochastic general-equilibrium model with housing and household debt, and compare the effectiveness of monetary policy, housing-related fiscal policy, and macroprudential regulations in reducing household indebtedness. The model features long-term fixed-rate borrowing and lending across two types of households, and differentiates between the flow and the stock of household debt. We use Bayesian methods to estimate parameters related to model dynamics, while level parameters are calibrated to match key ratios in the U.S. data. We find that monetary tightening is able to reduce the stock of real mortgage debt, but leads to an increase in the household debt-toincome ratio. Among the policy tools we consider, tightening in mortgage interest deduction and regulatory loan-to-value (LTV) are the most effective and least costly in reducing household debt, followed by increasing property taxes and monetary tightening. Although mortgage interest deduction is a broader tool than regulatory LTV, and therefore potentially more costly in terms of output loss, it is effective in reducing overall mortgage debt, since its direct reach also extends to home equity loans.
Keywords: E52; E62; R38; 330; Housing; Transmission of monetary policy; Financial system regulation and policies; Economic models